A experimental feasibility study of pre-stressed deep cold rolling - Lauw, Joshua (2015)
In the aerospace industry metal fatigue is the largest forms of failure in most aircraft components. Typically the most common area of metal fatigue occurs in the aircraft engines at the turbine blades. Several manufacturing process such as shot peening has proven to be able to impart compressive residual stresses into the metal surface to cause surface hardening which improves the fatigue life. A newer and proven process known as deep cold rolling is a cold work surface treatment which smoothens and hardens the metal surface by inducing compressive residual stresses similar to the shot peening process. In this preliminary study it sought to apply deep cold rolling unto pre-stressed surfaces by pre-bending the surfaces in various radiuses of curvatures. The differing radiuses of curvature directly correlate to a certain percentage value of the metal’s tensile yield stress. This study uses the material of almen A strips of SAE 1070 steel. By doing so this study aims to show if applying deep cold rolling work on pre-stressed steel is able to increase the amount of compressive residual stresses imparted to the steel strips. With more compressive residual stress it would theoretically improve the fatigue life of the metal by minimising cracks on the surface and preventing crack propagation due to a larger stress needed to overcome the compressive residual stress. The study has shown that with higher pre-stressed levels on the metal there is an increase in compressive residual stress imparted to the surface as shown by the larger values of post deep cold rolling arc heights of the almen strips.